STRUKTUR, KOMPOSISI DAN STATUS TUMBUHAN OBAT DL KAWASAN HUTAN TAMAN NASIONAL ALAS PURWO - HIDAYAT, SYAMSUL (Jurnal Biologi Udayana; Vol 12 No 1 (2008): JURNAL BIOLOGI, 2008)
Alas Purwo National Park is one of representative tropical low rain forests at eastern Java. There are many natural attractive sites and historical legend, which lead to, famous for ecotourisme activities. There are also rich of flora and fauna that some of them endemic and endangered species. Medicinal plant is one important material on the forest, which still unexplored more. Ten sampling transects were established in some sector of Alas Purwo for inventory of wild medicinal plants. The result shows that at least 5 species have been categorized as an endangered plant. Meanwhile, the structure and composition of endangered medicinal plants is not better than common medicinal plants.
Keywords: Alas Purwo; medicinal plant; endangered